Method for Dissemination of Results from Sample Survey of Innovation Activities at Enterprises for Population - Zhukovych, I. A.; Tereshchenko, G. I. (Statistics of Ukraine, 2017)
The procedure for application of survey results on general population, which is a key phase in the official statistical survey of innovation activities at enterprises, conducted on sample basis, is analyzed. The tool for conducting the survey in Ukraine is the questionnaire “Survey of Innovation Activities at Enterprises”, the analogue of the questionnaire used by the Community Innovation Survey. The survey is conducted once in two years by the methodological recommendations of the Community Innovation Survey. The sample survey of innovation activities at enterprises and application of its results for the general population involves computation of statistical weights as part of the indicators assessment. The following issues are reviewed: computation of basic weights of reporting units; editing of data obtained from the survey; correction of statistical weights to account for non-response and change of key parameters of enterprises. A central issue under discussion is quality control of the statistical weights system. Approaches to indicators assessment using the survey data are highlighted. Elaborated within the framework of the Strategy for Development of Official Statistics till 2017, this method is part of the methodological guidelines on the innovation statistics. Once used by the State Statistics Service of Ukraine, the method will enable for producing high quality statistical data on innovation activities at enterprises from the survey data, adapted to the standards of European statistics and fit for international comparisons, first and foremost with the analogous data of EU countries.